PENGARUH PRAKTIK KERJA DI UNIT PRODUKSI DAN PRAKTIK KERJA INDUSTRI TERHADAP KESIAPAN KERJA PADA SISWA KELAS XI DI SMK N 1 SURAKARTA TAHUN AJARAN 2017/2018 - -, Puspitaning Suci Rachmawati -; -, Baedhowi -; -, Salman Alfarisy Totalia - (Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
The research aims to determine: (1) The effect of work practices in production unit to the work readiness of student in class XI at Vocational High School 1 of Surakarta in academic year 2017/2018; (2)  The effect of industrial work practices to the work readiness of student in class XI at Vocational High School 1 of Surakarta in academic year 2017/2018; (3) The effect of work practices in production unit and industrial work practices to the work readiness of student in class XI at Vocational High School 1 of Surakarta in academic year 2017/2018).Population in this research is student in class XI at Vocational High School 1 of Surakarta in academic year 2017/2018 as many as 242 students. This research uses proportional random sampling sampling technique, so that there are 151 students selected to be samples. The research method used is a quantitative method with the type of expos facto research. Data collection was done by using questionnaire for work practices in production unit, industrial work practices dan work readiness. This research uses multiple linier regression analysis with significance level 0,05, then data processing has been obtained with the help of data program of SPSS (Statistical Product and Service Solution) version 22.The results of the research are as follows: Firstly, work practices in production unit have a significantly positive effect the work readiness of the students in class XI at Vocational High School 1 of Surakarta in academic year 2017/2018, as indicated by the value of tstat. =2,386 > that of tcrit.=1,976. Secondly, the industrial work practices have a significantly positive effect the work readiness of the students in class XI at Vocational High School 1 of Surakarta in academic year 2017/2018, as indicated by the value of tstat. =7,730> that of tcrit.=1,976 Thirdly, the work practices in production unit and industrial work practices have a significantly positive effect the work rediness of the students in class XI at Vocational High School 1 of Surakarta in academic year 2017/2018, as indicated by the value of Fstat. = 74,978 >that of Fcrit. = 3,057.